A short-range endemic species from south-eastern Atlantic Rain Forest shows deep signature of historical events: phylogeography of harvestmen Acutisoma longipes (Arachnida: Opiliones). Issue 2 (17th February 2018) - Peres, Elen Arroyo; DaSilva, Márcio Bernardino; Antunes, Manuel; Pinto-Da-Rocha, Ricardo
Abstract : The Brazilian Atlantic Rain Forest is amongst the most diverse biomes in the world, but the processes that shaped its biodiversity are still poorly understood. We used one mitochondrial and two nuclear markers to evaluate the phylogeographic patterns of the endemic harvestman Acutisoma longipes and its closely related species to investigate the biogeographic history of this biome. The results showed low intrapopulation diversity and strong population structure, suggesting poor dispersion amongst locations. Phylogenetic analyses pointed to three main mitochondrial lineages congruent with the geomorphology of the south-eastern region of Brazil (Serra do Mar, Serra da Mantiqueira, and interior plateau). These older divergences occurred in the middle-Neogene, suggesting that events in this period drove the diversification of the species, but Quaternary events also affected the populations locally. We detected some congruence between A. longipes demographic patterns and the areas of endemism delimited for harvestmen, suggesting that some regions of the distribution could have been more stable in the past (especially in Serra da Mantiqueira). Our findings corroborate that harvestmen are a suitable group for the study of ancient biogeographic events in the Atlantic Rain Forest, even at small-scale ranges. Acutisoma hamatum is here considered as a new junior synonym of A. longipes .